2023
DOI: 10.3390/insects14020183
|View full text |Cite
|
Sign up to set email alerts
|

Hemp Waste as a Substrate for Hermetia illucens (L.) (Diptera: Stratiomyidae) and Tenebrio molitor L. (Coleoptera: Tenebrionidae) Rearing

Abstract: The proper treatment of cannabis agricultural wastes can reduce the environmental impact of its cultivation and generate valuable products. This study aimed to test the potential of cannabis agricultural wastes as a substrate for the rearing of black soldier fly larvae (BSFL) and yellow mealworms (MW). In the case of BSFL, replacing the fibre component (straw) in the substrate with the hemp waste can increase the nutritional value of the substrate and led to bigger larvae. The bigger larvae had lower P and Mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
2
4
0
Order By: Relevance
“…As far as the protein content was concerned, BSFL contained 39.88 ± 2.97% of proteins expressed on DM. This value was close to the data obtained by Yakti et al [18], who grew BSFL on substrates containing hemp wastes and determined an average protein content of 37% on DM. Furthermore, similar results were also obtained by Surendra et al [4], who reported that BSFL developed on fruit and vegetable wastes contained proteins in amounts which ranged from 31 to 41% on DM.…”
Section: Black Soldier Fly Larva Compositionsupporting
confidence: 91%
“…As far as the protein content was concerned, BSFL contained 39.88 ± 2.97% of proteins expressed on DM. This value was close to the data obtained by Yakti et al [18], who grew BSFL on substrates containing hemp wastes and determined an average protein content of 37% on DM. Furthermore, similar results were also obtained by Surendra et al [4], who reported that BSFL developed on fruit and vegetable wastes contained proteins in amounts which ranged from 31 to 41% on DM.…”
Section: Black Soldier Fly Larva Compositionsupporting
confidence: 91%
“…In the presented study, the LN-2 larvae had higher protein concentration than the HN-2 larvae, which, in this case, cannot be explained by nutrients availability but is likely due to the dilution of proteins in the significantly higher larval biomass, or the different developmental stage of the larvae. This may also explain the higher P levels in the LN treatments as P has been shown to be more abundant in smaller larvae even when the initial substrate had higher P contents [ 31 ]. Generally, the presence of several elements in the larval biomass can be affected by the diet [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BSF colony used in this study was obtained from the Leibniz-Institute of Freshwater Ecology and Inland Fisheries (IGB) (Berlin, Germany) and was maintained in a rearing hall in Dahlewitz (Blankenfelde-Mahlow, Germany). The neonates used in the experiments were reared as described in Yakti et al [ 18 , 31 ] and received a chicken feed diet (Product name and batch: K (11 4) o.K., Agravis Raiffeisen AG, Velten, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The nutritional composition of BSF larvae is affected by the composition of the rearing substrate, which may vary in terms of macronutrient and mineral content [ 3 ]. Several studies have reported that BSF larvae are rich in CP and EE [ 1 , 9 , 26 , 27 ]. However, the composition of the rearing substrate can also impact nutrient accumulation in the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is a need for protein sources, including insects, algae, and mycoprotein, that are environmentally friendly and efficient [ 7 , 8 ]. The black soldier fly (BSF; Hermetia illucens ) has gained attention in recent years as a potential solution for sustainable agriculture [ 9 , 10 ]. The larvae of this species have been shown to have several benefits as a protein source, making them an attractive option for animal nutrition, thus addressing food security challenges [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%